2010
DOI: 10.1002/ptr.3325
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of bergamot oil on anxiety‐related behaviour and corticosterone level in rats

Abstract: Bergamot essential oil (BEO), Citrus aurantium subsp. bergamia (Risso) Wright & Arn. (Rutaceae), is used widely in aromatherapy to reduce stress and anxiety despite limited scientific evidence. A previous study showed that BEO significantly increased gamma-aminobutyric acid levels in rat hippocampus, suggesting potential anxiolytic properties. The aim of this study was to investigate the effect of BEO (1.0%, 2.5% and 5.0% w/w) administered to rats on both anxiety-related behaviours (the elevated plus-maze (EPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 29 publications
6
76
0
1
Order By: Relevance
“…Besides EOCA and EOCL, other EOs that showed anxiolytic-like effects in animal models, such as C. x aurantium, C. x reticulata, Foeniculum vulgare and Lippia alba (limonene-carvone chemotype), have limonene as a major component (Gargano et al, 2008;Faturi et al, 2010;Saiyudthong, Marsden, 2011;Hatano et al, 2012;Mesfin et al, 2014). Limonene directly binds to the adenosine A 2A receptor, which may induce sedative effects (Park et al, 2011) and also demonstrated direct vasorelaxant effects (Kang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides EOCA and EOCL, other EOs that showed anxiolytic-like effects in animal models, such as C. x aurantium, C. x reticulata, Foeniculum vulgare and Lippia alba (limonene-carvone chemotype), have limonene as a major component (Gargano et al, 2008;Faturi et al, 2010;Saiyudthong, Marsden, 2011;Hatano et al, 2012;Mesfin et al, 2014). Limonene directly binds to the adenosine A 2A receptor, which may induce sedative effects (Park et al, 2011) and also demonstrated direct vasorelaxant effects (Kang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments are needed to elucidate the mechanisms through which BEO modulates autophagy and to assign a potential role for this process in the pharmacological effects of BEO reported in animal models of diseases, including anxiety [20], cerebral ischemia [18] or pain [15], [21].…”
Section: Discussionmentioning
confidence: 99%
“…The latter point has been addressed by a number of studies which, indeed, documented that BEO may affect synaptic transmission in rodents. In fact, BEO modulates release of specific amino acid neurotransmitters in discrete brain regions under both basal [17] and pathological conditions [18], produces a dose-related sequence of sedative and stimulatory behavioural effects in normal rats [19], exerts anxiolytic effects in the elevated plus-maze and hole-board tests [20] and neuroprotective effects against exicitotoxic [18], nociceptive [21] and allodynic stimuli [15], yet the underlying molecular mechanisms have not been conclusively established and need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Today, it is widely used in aromatherapy for reducing stress and anxiety [3]. According to most recent research, it counteracts anxiety behavior in rats via the stress response pathway, reducing the activity of the hypothalamus-pituitary-adrenocortical axis (HPA) [3].…”
Section: Introductionmentioning
confidence: 99%
“…), which belongs to the Citreae tribe in the Aurantioideae subfamily of the Rutaceae plant family, originates from the Mediterranean ecoregion, particularly from southern Italy and Greece. Its volatile oil, which is produced from the exocarp by means of cold pressing [1], is in high demand for a wide range of perfumes, cosmetics, and especially for aromatherapy [2,3]. …”
Section: Introductionmentioning
confidence: 99%